The Impact of Employee Satisfaction, Organizational Commitment, Job Performance and Teamwork as the Success Factors in FedEx: A Study of FedEx’s Employees in Malaysia - Qing, Koh Jhee; Kee, Daisy Mui Hung; Soon, Joel Chen Tai; Hui, Chin Kah; Kelvin, Ch’ng; Singh, Abishek; Kurniawan, Obaja Elka; Alotaibi, Aisha Bader; Pandey, Rudresh; Quttainah, Majdi Anwar; Sin, Liem Gai (AIBPM Publisher, 2020)
In 1971, FedEx was founded as Federal Express Corporation, by Frederick W. Smith. In the world of supply chain services, FedEx is one of the most trusted and respected brands. The main goal of FedEx is to make sure that FedEx is their customers' first choice, by delivering world-class customer experience. FedEx ensures that they deliver world-class customer experience to their customers so that their loyalty towards FedEx will grow and they will not risk trying another carrier service. FedEx takes care of its people first, believing they will then take care of its customers. For this reason, FedEx top leaders commit the “People First” philosophy.